Legal Study of Dzurri Waqf and its Implementation towards Strengthening High Heritage Assets in Minangkabau, West Sumatra, Indonesia - Ahmad Wira; Nurul Huda; Ahmad Sunawari Long; Wahyuni Lely Augusna; Meirison Meirison; Yenti Afrida (JURIS (Jurnal Ilmiah Syariah), 2023)
One concept of preserving family assets can be carried out through the practice of dzurri waqf. In Minangkabau, preservation of family assets is carried out in the form of high inheritance management. This article aims to discuss the legal concept of dzurri waqf and its implementation in high inheritance management in Minangkabau, West Sumatra. The findings of this study are very specific because the Minangkabau culture adheres to on one side, a matrilineal system but on the other hand, is based on the Islamic law. The data in this study were obtained through in-depth interviews with four experts, i.e., the expert council of MUI West Sumatra, the Chair of the West Sumatra Indonesian Waqf Board, the Chair of West Sumatra Nazir, and the expert council of the Lembaga Kerapatan Adat Alam Minangkabau (LKAAM) West Sumatra. This study found that first, the concept of dzurri waqf is identical to the management of high heirloom assets in Minangkabau. It is proven by some asset management that is almost the same as dzurri waqf, i.e., the element of property must be retained in principal and from the element of beneficiaries (mauquf alaih) who are family members. Second, there is a strategy to maintain high pusako treasures through religion, namely by managing high pusako treasures, such as dzurri waqf management so that the identity of high pusako treasures as culture can survive and be managed sustainably. Third, in order to maintain the identity of the high pusako treasure, the nazir in the context of dzurri waqf is appointed from the niniak mamak component as the holder of the power of the high pusako treasure.